A Analytical Study Of Selected Scripts in Pashtu Language on Quranic Correlation and Cohesive Harmony of the Ulema of Khyber Pakhtunkhwa.: پشتوزبان میں نظم قرآن پر علماء خیبر پختونخوا کی منتخب تصانیف کےمناہج کاایک تجزیاتی مطالعہ - Swati, Aftab Ahmad; Hassan, Dr. Najmul; Khan, Dr. Janas (Al Khadim Research Journal of Islamic Culture and Civilization, 2021)
Since Quran, being the words of Allah the almighty, has been bestowed in Arabic Language,a part from other multiplesupernatural characteristics. Quran has Drawn its message very cohesively where any word or sentence is connected with another word, verses or concepts in a very meaningful manner. Keeping in view the importance of Correlation and Cohesion in the Holy Quran, it has attracted the attention of various scholars and researchers. The following research paper aims at exploring the contribution of the Ulema of Khyber Pakhtunkhwa in this Field. For this purposeFive scripts have been selected to point out the importance of the correlation and systematic meaningful relation among the verses and words of Allah which testifies that the Holy Quran is the revealed book. It is found that the Holy Quran contains cohesive harmony which reveals the fluency of Arabic language as well.